2017
DOI: 10.1111/ijfs.13469
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of physico‐chemical properties and antioxidant activity of freeze‐dried mung bean (Vigna radiata) and adzuki bean (Vigna angularis) sprout hydrolysate powders

Abstract: Summary Mung bean (MB) and adzuki bean (AZB) sprouts were hydrolysed with Flavourzyme® at four different concentrations for 6 h. Nongerminated beans subjected to each enzyme concentrations were set as the control. For both bean sprouts, the highest amounts of free amino group, total free amino acids and total phenolic content (TPC) were obtained with 7% (w/w) Flavourzyme®. Each bean sprout hydrolysate was subjected to freeze‐drying in absence and presence of 5% maltodextrin (w/v). The addition of maltodextrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
3
18
0
1
Order By: Relevance
“…Similar results were obtained previously for other foods such as cereals (Pérez‐Jiménez & Saura‐Calixto, ). Enzymatic hydrolysis of mung bean and adzuki bean also resulted in an increased release of polyphenols previously (Sangsukiam & Dungmal, ). However, results contrast with those reported by Zhang et al .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar results were obtained previously for other foods such as cereals (Pérez‐Jiménez & Saura‐Calixto, ). Enzymatic hydrolysis of mung bean and adzuki bean also resulted in an increased release of polyphenols previously (Sangsukiam & Dungmal, ). However, results contrast with those reported by Zhang et al .…”
Section: Resultsmentioning
confidence: 93%
“…Although the current study included a protein precipitation step, in order to avoid the interference of proteins with the TPC determination method, short peptides could still be soluble at high salt concentrations. Thus, the observed increase in antioxidant capacity could be also attributed to the generation of antioxidant peptides, as pulses are protein‐rich foods (Nosworthy et al ., ) and excellent sources of bioactive peptides (Sangsukiam & Dungmal, ).…”
Section: Resultsmentioning
confidence: 99%
“…In all varieties, much higher amounts of polyphenols were released upon in vitro digestion in comparison to domestic processing and methanolic extraction. Previous studies have also shown that enzymatic hydrolysis of legumes, including beans, results in higher polyphenol release in comparison to solvent extraction (Lafarga et al, 2019;Perez-Hernandez et al, 2020;Sangsukiam & Duangmal, 2017). Polyphenols bound to polysaccharides and proteins require hydrolysis by digestive enzymes or intestinal microorganisms before being absorbed (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Electron Spin Resonance (ESR), a technique detecting and identifying molecules containing unpaired electrons, can identify various types of free radicals such as DPPH radicals, carbon‐centred radicals, and hydroxyl radicals. Sangsukiam & Duangmal () reported that ESR technique showed advantages over colorimetric assay in the measurement of antioxidant activity of freeze‐dried mung bean and adzuki bean sprout hydrolysate powders as some interference occurring during discoloration of DPPH free radicals measurement could be reduced. ESR technique was applied to study the antioxidant activity (DPPH radical, methyl, hydroxyl and superoxide anions scavenging activity) of some unifloral honeys (Inoue et al ., ).…”
Section: Introductionmentioning
confidence: 99%